Evaluation of the TOD Concept in the Area of Tanjung Barat, Pondok Cina, and Rawa Buntu Station - Akmal Rasyad Permana; Yohanes Basuki Dwisusanto (Jurnal Impresi Indonesia, 2025)
Transit-Oriented Development (TOD) offers a potential solution to traffic congestion driven by urban growth, particularly in the area of public transportation. PT KAI and Perumnas have pursued TOD by developing mixed-use areas integrated with train stations to enhance access to surrounding neighborhoods. This study examines the implementation and development potential of TOD at three sites: Tanjung Barat, Pondok Cina, and Rawa Buntu stations. Using a comparative evaluative method, each site was assessed based on the eight TOD principles defined by the ITDP: walk, cycle, connect, transit, mix, densify, compact, and shift. The results show that none of the sites fully implement all eight principles, with scores only reaching the minimum threshold of the Standard Bronze category. Rawa Buntu Station failed to meet even this minimum standard, while the highest score was achieved by the TOD apartment area at Pondok Cina Station, followed by Tanjung Barat. Score differences were mainly influenced by the diversity and quality of surrounding functions, facilities, and infrastructure.